Association between the scores of the Japanese version of the Brief Assessment of Cognition in Schizophrenia and whole‐brain structure in patients with chronic schizophrenia: A voxel‐based morphometry and diffusion tensor imaging study. Issue 12 (10th September 2017) - Hidese, Shinsuke; Ota, Miho; Matsuo, Junko; Ishida, Ikki; Hiraishi, Moeko; Teraishi, Toshiya; Hattori, Kotaro; Kunugi, Hiroshi
Abstract : Aim: The Brief Assessment of Cognition in Schizophrenia (BACS) is a concise tool designed to evaluate cognitive deficits in schizophrenia. We examined the possible association between BACS scores and whole‐brain structure, as observed using magnetic resonance imaging with a relatively large sample. Methods: The study sample comprised 116 patients with schizophrenia (mean age, 39.3 ± 11.1 years; 66 men) and 118 healthy controls (HC; mean age, 40.0 ± 13.6 years; 58 men) who completed the Japanese version of the BACS (BACS‐J). All participants were of Japanese ethnicity. The magnetic resonance imaging volume and diffusion tensor imaging data were processed with voxel‐based morphometry and tract‐based spatial statistics, respectively. Results: There were significant reductions in the regional gray matter volumes and white matter fractional anisotropy values in patients with schizophrenia compared to HC. For the gray matter areas, the working memory score had a significant positive correlation with the anterior cingulate and medial frontal cortices volumes in the patients. For the white matter areas, the motor speed score had a significant positive correlation with fractional anisotropy values in the corpus callosum, internal capsule, superior corona radiata, and superior longitudinal fasciculus in the patients. However, there was no significant correlation among either the gray or white matter areas in the HC. Conclusion: Our results suggest that among the BACS‐J measures, the working memory and motor speed scores are associated with several structural alterations in the brains of patients with schizophrenia.